The Impact of the Mix Marketing to Higher Education in Raising the Level of Quality from the Students Perspective in Algerian Universities - Hamidi Zeggai (University of Science and Technology, Yemen, 2015)
This study aimed to highlight the reality of university services marketing by focusing, mainly, on each element of the marketing mix in its seven in order to upgrade the level of performance of the product quality of education in all its components .conducting of the study is applied on one of our university facilities and made the students of the university in Saida Algeria an element of focus. A questionnaire was distributed consisting on (35) questions, to be answered by (130) students. The analysis according to the student's answers to the yield a number of scientific conclusions such us: 1- There is a strong correlation between the application of the elements of the marketing mix and improving the quality of educational services. 2- The results showed that members of the service providers of the faculty, administration and library workers, and all the staff of the university have significant influence on in upgrading the quality of higher education services. 3- The results also showed the impact of the equipment and the physical meaning of the Service on the level of the quality of higher education services. 4- The results showed that the adoption modern methods in the field of distribution and promotion services increase the quality of higher education services.